MODERASI BERAGAMA DAN LITERASI KEAGAMAAN: RESPON SISWA MADRASAH TERHADAP ISU RADIKALISME DAN INTOLERANSI - Dianto, Icol; Fikri, Sholeh; Siregar, Martua Haholongan; Efendi, Erwin; Dalimunthe, Tua (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the level of understanding of Madrasah Aliyah Negeri 3 Central Tapanuli students about religious moderation, religious literacy, and response to the issue of radicalism in the madrasah environment. The research approach uses a qualitative method strengthened with quantitative data through the distribution of a Likert scale questionnaire to 25 grade XII students. The data was analyzed descriptively by reviewing four main indicators: religious moderation, religious literacy, radicalism and attitudes towards differences, as well as social media and digital moderation. The results of the study showed that all aspects were in the "Agree" category with an average score above 3.9, indicating students' positive attitudes towards the values of moderation, tolerance, and digital religiosity. Community service programs implemented through the blended learning model  have proven to be effective in increasing students' awareness of religious moderation and religious literacy. These findings show a strong relationship between religious literacy and moderate attitudes in rejecting radicalism. Students with high literacy levels are more critical of religious content and are able to select information wisely on social media. This study recommends strengthening the religious moderation curriculum and religious digital literacy training to strengthen the ideological resilience of madrasah students in the digital era.